A FAILURE MODE AND EFFECT ANALYSIS ON WATER RECIPROCATING PUMP FOR DRILLING INDUSTRY - Satria, Adam (Jurnal Ilmiah Informatika Komputer, 2017)
Pumps  have been designed for a variety of purposes that operate to move liquid on high elevation and high pressure. One of them is a positive-displacement reciprocating duplex power pump. In drilling industry, it is used to circulate clean water to the supply tank, and to mix mud while simultaneously drilling. A Failure Mode and Effect Analysis (FMEA) was carried out on these pumps to analyze potential failures. In this study, the data of pump’s failures, occurrences, and detection methods were collected from PT Airtara Bekasi and interpreted on a criteria rank system to determine its Risk Priority Number (RPN). Discussions on recommended actions to decrease failure risks were conducted in brainstorming meetings. Of the whole RPN results, the highest score which was scored 224 was found in a Silicon-Controlled Rectifier. To reduce RPN score of this pump, several steps were applied, namely: installed bridge diode to reduce ripple wave on converted DC waveform, installed fuse current to prevent damage from shorting, improved the quality of drive current, and implemented proper installation circuit diagram. The FMEA was then repeated to determine the new score of revised RPN. It decreased significantly from 224 to 54 or it had about 76% reduction. Keywords: Failure Mode and Effect Analysis, FMEA, Positive-Displacement Pump, Power Pump, Reciprocating Pump